2021
DOI: 10.1016/j.annonc.2021.08.2112
|View full text |Cite
|
Sign up to set email alerts
|

LBA35 Avelumab-cetuximab-radiotherapy versus standards of care in patients with locally advanced squamous cell carcinoma of head and neck (LA-SCCHN): Randomized phase III GORTEC-REACH trial

Abstract: Background: Based on a potential synergistic effect of antiePD-L1 avelumab plus cetuximab and radiotherapy (RT), this combination was tested in a randomized phase III trial against 2 standards of care (SOC) in LA-SCCHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Early results from these trials are indicative that hypofractionated RT can induce a larger immune response and enhance the effects of immunotherapy compared to conventional RT 4,15 (NCT03635164). As all clinical trials using immunotherapies combined with traditional RT have failed in HNSCC 4,55 , we expect that these findings will be of high translational relevance in the setting of hypofractionated RT. Despite these limitations, our data strongly support future HNSCC clinical trial design with lymphatic sparing approaches and hypofractionated RT, particularly in the context of immunotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…Early results from these trials are indicative that hypofractionated RT can induce a larger immune response and enhance the effects of immunotherapy compared to conventional RT 4,15 (NCT03635164). As all clinical trials using immunotherapies combined with traditional RT have failed in HNSCC 4,55 , we expect that these findings will be of high translational relevance in the setting of hypofractionated RT. Despite these limitations, our data strongly support future HNSCC clinical trial design with lymphatic sparing approaches and hypofractionated RT, particularly in the context of immunotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…With the future looking into immunotherapy (immune checkpoint inhibitor drugs targeting PD-1or PD-L1), a novel concept of combining immunotherapy with anti-EGFR agent and RT is hypothesized as anti-EGFR agents also act by immune modulation. The REACH study by the GORTEC group - Randomized Trial of Avelumab-Cetuximab-Radiotherapy Versus standard of care (CCRT) in LA-HNC, whose interim data was recently presented as an abstract [55] , showed that the combination of anti PD-L1 – Avelumab plus Cetuximab and RT did not improve PFS (1 year PFS 64% v/s 73%; HR-1.27) and was found to be futile when compared to standard of care, especially in the cohort which used Cisplatin based CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are ongoing trials with combination approaches using immunotherapy, the vast majority of them use immunotherapy in combination with chemotherapy in the metastatic setting or after chemoradiation in the adjuvant setting. The recent JAVELIN Head and Neck 100 and GORTEC‐REACH trials investigated avelumab with chemoradiation in locally advanced HNSCC, but failed to meet their primary PFS endpoints 19–21 . However, the majority of patients in each study had oropharyngeal cancer, which could have masked the benefit of concurrent immunotherapy given the more favorable prognosis at this subsite.…”
Section: Discussionmentioning
confidence: 99%
“…The recent JAVELIN Head and Neck 100 and GORTEC-REACH trials investigated avelumab with chemoradiation in locally advanced HNSCC, but failed to meet their primary PFS endpoints. [19][20][21] However, the majority of patients in each study had oropharyngeal cancer, which could have masked the benefit of concurrent immunotherapy given the more favorable prognosis at this subsite.…”
Section: Toxic Effectsmentioning
confidence: 99%